Meningkatkan Penguasaan Konsep Bilangan Pada Anak Tunarungu Melalui Permainan Dhakon - Farida Yuliati (Universitas Muhammadiyah Surakarta, 2014)
This research aims to improve the mastery of concepts for the deaf children of class 1 through dhakon game. This research used the classroom action research approach by planning, actuating, observation, and reflection. The subjects in this study were all students in grade 1 SLB B YPALB Karanganyar, totaling 4 children. The techniques of collection data was done by observation, interviews (conversations) and documentation. Data validity used triangulation techniques, and the analysis of data used descriptive qualitative. The results of the research on first cycle, showed that all children increased in their values, 3 children, increased the value of 1 point and 1 child increased 2 points with an average value of 6, in the range of 40% P d” 60%. The achievement of performance indicators category was enough. Despite the increase in value, but there was one child whose value was less than 6 (KKM). In the second cycle, 2 childres value increased by 1 point and 2 childrens increased the value of 2 points with an average value of 7.5, so it is in the range of 60% P d” 80% with the category of high performance achievement indicators. No value below 6 (KKM). In the second cycle of the increase in value was set 60% P d” 80% or ‘high’. The conclusion of the study, there was an increase in numbers for students mastery of concepts in SLB-B class I YPALB Karanganyar after the action through dhakon game.